Application of Local Materials in the Renovation Design of Local Buildings. Issue 2 (March 2021) - Wu, Chuntao
Abstract: In the process of urbanization, the gradual loss of the characteristics of traditional villages caused by the destruction of environmental resources calls for the attention to return to pursue the essence of traditional village architecture as well as traditional building renovation and environmental coordination. Through the study of the characteristics, craftsmanship and aesthetics of the local materials, the transformation and design of the local buildings with the theory of oriental design are used to show the coexistence of the local customs, architectural characteristics and natural environment. Through the experimental study on the application of local materials in this paper, the design strategy of local materials for the transformation of traditional buildings is summarized to protect and inherit Chinese local buildings, which has a deep developmental significance to the transformation and application architectures in future.